2020
DOI: 10.1177/2048872619882363
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of GRACE risk score in Takotsubo syndrome

Abstract: Background: Takotsubo syndrome is an increasingly recognised cardiac condition that clinically mimics an acute coronary syndrome, but data regarding its prognosis remain controversial. It is currently unknown whether acute coronary syndrome risk scores could effectively be applied to Takotsubo syndrome patients. This study aims to assess whether the Global Registry of Acute Coronary Events (GRACE) score can predict clinical outcome in Takotsubo syndrome and to compare the prognosis with matched acute coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
(41 reference statements)
3
19
0
Order By: Relevance
“…Hence we hypothesize that, in the vulnerable subset of patients with dyspnea at presentation, comorbidities may act in a synergistic fashion with TTS functional abnormalities, resulting in greater cardiac dysfunction and decompensation during the acute phase, and worse prognosis in the long-term. Accordingly, the prognostic relevance of comorbidities is supported by results of both our and other studies 14 , 35 37 , and further corroborated by the fact that long-term mortality in TTS is mainly non-cardiovascular 6 , 10 , 24 , 29 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Hence we hypothesize that, in the vulnerable subset of patients with dyspnea at presentation, comorbidities may act in a synergistic fashion with TTS functional abnormalities, resulting in greater cardiac dysfunction and decompensation during the acute phase, and worse prognosis in the long-term. Accordingly, the prognostic relevance of comorbidities is supported by results of both our and other studies 14 , 35 37 , and further corroborated by the fact that long-term mortality in TTS is mainly non-cardiovascular 6 , 10 , 24 , 29 .…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, long-term mortality rate was higher in patients exhibiting dyspnea at presentation, even after excluding those events during the first month, with mortality curves progressively diverging during follow-up. These findings indicate that TTS patients admitted with symptoms of decompensated heart failure suffer a worse prognosis even after LV systolic function is expected to have largely recovered, in keeping with a significant body of evidence suggesting that in TTS the severity of cardiac involvement correlates with worse prognosis in the long-term [24][25][26][27][28][29][30] . One potential explanation is that dyspnea at presentation, being associated to higher degree of cardiac dysfunction, represents a marker of more severe TTS episodes that can lead to long-term sequelae and subsequent heart failure phenotype 31 .…”
Section: Discussionsupporting
confidence: 74%
“…The majority of current studies suggest that older TCM patients have worse long-term outcomes than younger patients. 22,26,27,41,42,44,[47][48][49]55,56,62,[71][72][73][74][75][76][77][78] Cammann et al found that elderly patients with TCM (≥75 years old) had a higher long-term (>60 days) mortality rate (P < 0.001) than younger (≤50 years old) and middle-age patients (51 to 74 years old). 27 Similarly, another study found that older TCM patients had a higher 1 year mortality rate in both primary (12.5% in ≥85 years old vs. 7.0% in 75-84 vs. 5.3% in 65-74, P < 0.05) and secondary TCM patients (16.0% vs. 11.6% vs. 9.6%, P < 0.05), in a large sample of 19 966 TCM patients.…”
Section: Agementioning
confidence: 99%
“…On the same line, in the paper of Scudiero et al, 15 when the Global Registry of Acute Coronary Events (GRACE) score was applied not only in 300 acute coronary syndrome patients, but also in 300 takotsubo patients, a physical trigger was mostly detected in the higher GRACE score risk quartile, while takotsubo related to emotional triggers had an inverse relationship. The authors confirm that, considering the old age and high comorbidities, takotsubo mortality was driven by non-cardiovascular death.…”
mentioning
confidence: 92%